Sensor and sensor response-issues and interfacing - Ahmmad, Syed Masrur; Khan, Sheroz; Nordin, Anis Nurashikin; Khan, Md Rasiuddin (IIUM Press, 2011)
The chapter presents the basic concepts of sensors and their response. Also the nonlinearity issues caused by the response are detailed with relative discussion and results. The errors obtained in the results are analysed as well